The blink and the bliss of Being (in memory of Alexander Antonovich Oborin) - Ivshina , I.B. (Perm Federal Research Centre Journal, 2023)
The spectrum of this essay represents a specific historical stage in the development of only one direction of the whole variety of scientific areas developed by Prof. A.A. Oborin, concerning the problems of widespread use of the microbiological method of oil and gas prospecting in the general complex of oil and gas prospecting geochemistry.